Functional compensation and pronominal subject "tú" in Cuban Spanish - Sánchez Arroba, María Elena (2013)
The basic linguistic characteristics of Caribbean Spanish, particularly those of Cuban Spanish, are listed, and one characteristic syntactic feature of this dialect of Spanish is presented; namely, the frequent use of pronominal subjects. A description is given of the behavior of the second person singular subject pronoun “tú” in the oral corpus based on fourteen interviews with well-educated speakers of Havana, Villa Clara, and Matanzas, linking the frequent appearance of this pronoun with the Functional Compensation Hypothesis. Verification is made of an increase in frequency of the use of the subject pronoun “tú”, when the morphemic verbal marker of the second person singular elides, but the lineal regression analysis does not indicate the pertinence of that morphophonological dependent variable for the expression of those subjects. On the contrary, the factor with the most predictive weight for the the subject “tú” expression in Cuban Spanish is the pragmatic variable of partial change in reference, a fact that coincides with other non-Caribbean Spanish dialects.